A Psychometric Evaluation of the Adapted Dyadic Self-Care in Transplant Scale - Brittany Koons; Rachel Lehman; Subhash Aryal; Barbara Riegel; Harleah Buck (Journal of Nursing Measurement, 2026)
Background and Purpose: Verification of a caregiver is required for transplant listing; however, no tool assesses how patient–caregiver dyads manage transplant care. This study adapted and validated the Dyadic Self-Care in Transplant (D-SCIT) scale. Methods: This was a cross-sectional study of 50 lung transplant patient–caregiver dyads. Content validity was assessed through cognitive interviews, and construct validity was assessed by examining the association between dyad type and relationship mutuality. Results: Dyads completed the D-SCIT with ease, confirming content validity. Congruent dyads were positively correlated with the dyadic mean mutuality score (0.17) and negatively correlated with dyadic incongruence in mutuality (−0.10), demonstrating convergent validity. Conclusions: This study provides preliminary validation of the D-SCIT to assess how transplant dyads engage in transplant self-care, addressing a clinical and research gap.